Telepathy - Conrad, Burton Wesley (My University, 1895)
Introduction: Within the mental chambers of every persons mind there lingers thoughts on a vast number of subjects they are skeletons whose existence have been known in all ages. They are nature’s workings, yet the bans relating to these forms have to be studied and reduced to certainty and system.
Citation: Conrad, Burton Wesley. Telepathy. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: The mind; Telepathy; Nature; Theses; Manuscripts (documents)